Immunomodulation by dietary supplements: A preventive health strategy for sustainable aquaculture of tropical freshwater fish, Labeo rohita (Hamilton, 1822). (9th June 2021) - Gupta, Akruti; Gupta, Sanjay Kumar; Priyam, Manisha; Siddik, Muhammad A.B.; Kumar, Neeraj; Mishra, Prashant Kumar; Gupta, Kishore Kumar; Sarkar, Biplab; Sharma, Tilak Raj; Pattanayak, Arunava
Abstract: Dietary supplementation is an effective strategy for boosting the innate immune response in fishes. It involves the use of functional ingredients that bear the potential for mitigating the deleterious effects of chemotherapeutics (bioaccumulation and development of drug‐resistant pathogens), as a more ecologically responsible approach to fish farming. With the emergence of probiotics, prebiotics, synbiotics and herbal immunostimulants; dietary supplementation has become an integral aspect of immuno‐nutrition. In this review, we have compiled a list of dietary immunostimulants in rohu, based on the research carried over the last ten years. It should be noted that nearly 25% of the studies on dietary supplementation in Labeo rohita investigated probiotics species (either singly or as mixtures), followed by the use of herbal supplements or phytobiotics. In relation to stress, about 30% of the studies dealt with the supplementation of tryptophan, followed by the incorporation of lipotropes. Moreover, approximately 55–60% of the studies reviewed, were restricted to nutrition‐based disease resistance against Aeromonas hydrophila infection. Commercially available probiotics and herbal feed additives have been helpful in the health management of L. rohita to some extent. Ongoing research is consistently exploring novel ingredients inducing favourable immunomodulation to survive stress and widespread A . hydrophila infection in L . rohita . However, further investigations aiming at broad‐spectrum disease resistance and multiple stress resilience are recommended. Efforts must also be directed towards the elucidation of specifically targeted response in vivo. Overall, greater insights into the molecular mechanisms of dietary supplementation of immunostimulants warrants the use of downstream analytical techniques and high‐throughput screening tools.